Hubungan Tingkat Kepatuhan Minum Obat Dengan Data Hasil Laboratorium Pasien Tuberkulosis di Puskesmas Padangan - Rachma, Nur Isnaini Alfiyatur; Hutahaen, Titi Agni; Pitaloka, Ria Indah Kusuma (Jurnal Lentera Farma, 2026)
Mycobacterium tuberculosis is the infectious agent that causes tuberculosis (TB), which is still a serious public health concern in Indonesia. Patients' adherence to Anti-Tuberculosis Drug (ATD) therapy is crucial to the success of tuberculosis treatment because non-adherence can result in treatment failure, disease recurrence, and drug resistance. The purpose of this study was to ascertain the degree of medication adherence among tuberculosis patients at Padangan Public Health Center and to examine the connection between medication adherence and laboratory result data. This study used a cross-sectional design, a quantitative method, and an analytical observational design. Thirty tuberculosis patients who satisfied the inclusion criteria made up the sample. The Medication Adherence Report Scale-5 (MARS-5) questionnaire was used to measure medication adherence, and patient medical records were used to gather laboratory results, such as Molecular Rapid Test (TCM) and Acid-Fast Bacilli (AFB) examination results. The Chi-Square test with a 95% confidence level was used to examine the data. According to the findings, 7 respondents (23.3%) were classified as non-adherent, whereas 23 respondents (76.7%) were classified as adherent. Compared to non-adherent individuals, the majority of adherent patients showed superior test results. Medication adherence and laboratory results data among tuberculosis patients at Padangan Public Health Center are significantly correlated, according to the Chi-Square test, which produced a significance value of p = 0.001 (p < 0.05). In conclusion, among tuberculosis patients, medication adherence was substantially correlated with laboratory results. Therefore, to increase adherence and maintain the effectiveness of tuberculosis therapy, ongoing education, monitoring, and patient care are required. Mycobacterium tuberculosis adalah agen infeksius penyebab tuberkulosis (TB), yang masih menjadi masalah kesehatan masyarakat yang serius di Indonesia. Kepatuhan pasien terhadap Obat Anti-Tuberkulosis (OAT) sangat penting untuk kemanjuran pengobatan TB karena ketidakpatuhan dapat mengakibatkan kegagalan terapi, kekambuhan, dan resistensi obat. Tujuan penelitian ini adalah untuk mengetahui tingkat kepatuhan pengobatan dan meneliti korelasi antara kepatuhan pengobatan dan data laboratorium pasien tuberkulosis di Puskesmas Padangan. Penelitian ini menggunakan metodologi kuantitatif dengan pendekatan cross-sectional dan desain analitik observasional. Tiga puluh pasien tuberkulosis yang memenuhi kriteria inklusi menjadi sampel penelitian. Hasil tes Molecular Rapid Test (TCM) dan Acid-Fast Bacilli (AFB) diperoleh dari rekam medis pasien, dan kuesioner Medication Adherence Report Scale-5 (MARS-5) digunakan untuk mengukur tingkat kepatuhan. Uji Chi-Square dengan tingkat kepercayaan 95% digunakan untuk menganalisis data. Berdasarkan temuan, 7 responden (23,3%) tidak patuh, sedangkan 23 responden (76,7%) patuh. Dibandingkan dengan individu yang tidak patuh, mayoritas pasien yang patuh memiliki hasil tes yang membaik. Tingkat kepatuhan pengobatan dan data laboratorium pasien tuberkulosis di Puskesmas Padangan berkorelasi signifikan, menurut hasil uji Chi-Square, yang menunjukkan nilai signifikansi p = 0,001 (p < 0,05). Temuan penelitian menunjukkan bahwa tingkat kepatuhan pengobatan sangat berkorelasi dengan data laboratorium pasien tuberkulosis, sehingga memerlukan edukasi, pemantauan, dan dukungan pasien lebih lanjut.